Aberrant regional neural fluctuations and functional connectivity in generalized anxiety disorder revealed by resting-state functional magnetic resonance imaging. (15th June 2016) - Wang, Wei; Hou, Jingming; Qian, Shaowen; Liu, Kai; Li, Bo; Li, Min; Peng, Zhaohui; Xin, Kuolin; Sun, Gang
Highlights: Generalized anxiety disorder patients show abnormal amplitude of low frequency fluctuations and functional connectivity in several brain regions. Abnormal functional connectivity in prefrontal-limbic and cingulate networks correlated with clinical symptoms severity in generalized anxiety disorder patients. Aberrant prefrontal-limbic and cingulate networks might underlie the neural mechanisms of generalized anxiety disorder. Abstract: The purpose of this study was to investigate the neural activity and functional connectivity in generalized anxiety disorder (GAD) during resting state, and how these alterations correlate to patients' symptoms. Twenty-eight GAD patients and 28 matched healthy controls underwent resting-state functional magnetic resonance (fMRI) scans. Amplitude of low-frequency fluctuation (ALFF) and seed-based resting-state functional connectivity (RSFC) were computed to explore regional activity and functional integration, and were compared between the two groups using the voxel-based two-sample t test. Pearson's correlation analyses were performed to examine the neural relationships with demographics and clinical symptoms scores. Compared to controls, GAD patients showed functional abnormalities: higher ALFF in the bilateral dorsomedial prefrontal cortex, bilateral dorsolateral prefrontal cortex and left precuneus/posterior cingulate cortex; lower connectivity in prefrontal gyrus; lower in prefrontal-limbic and cingulate RSFC and higher prefrontal-hippocampus RSFC were correlated with clinical symptoms severity, but these associations were unable to withstand correction for multiple testing. These findings may help facilitate further understanding of the potential neural substrate of GAD.